Governança corporativa em empresas familiares de capital fechado: estudo de caso da empresa Pinamak Soluções em Logística para o segmento de petróleo - Pina, André Pereira Antunes (2011)
Although the theme of corporate governance is recent in the country and in the world, many family-controlled companies, medium and large companies, have adopted its mechanisms, especially the establishment of Boards of Directors or Advisory Councils, given the importance that the governance has taken on in academia and business. In this sense, there was a case study in a family business in order to identify the conditions that drive the privately held family company to implement the modern corporate governance structures. We used semi-structured questions divided into three groups of factors (assumptions), business, family and corporate. The results of the case study indicated the family factors as the major drivers of development of corporate governance in privately held family business, in both public investigation, both employees and family members. Then came the corporate factors. The business factors were in last place.